Potentially reversible causes of dementia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Wai, Kyaw Thun; Abdul Rashid, Mohd Amran; Akter, Seikh Farid Uddin; Musa, Ramli (International Online Medical Council (IOMC), 2010)
Introduction: Dementia is tragic mind-wrecking disease, defined as a multifaceted decline in cognitive function severe enough to interfere with activities of daily life. Three individual cases are presented that presented with loss of memory and altered behaviour. Even though potentially reversible dementia accounts for a relatively small portion of the total cases of dementia, the three cases presented here demonstrate that accurate and timely diagnosis may greatly improve the condition of the patients, or even restore their normal intellectual function.